Healthcare service utilization of hill tribe children in underserved communities in thailand: Barriers to access - Katemanee Moonpanane; Khanittha Pitchalard; Jintana Thepsaw; Onnalin Singkhorn; Chomnard Potjanamart (BMC, 2022)
Abstract Background Hill tribe children, an ethnic minority group in Thailand, experience wide-ranging social and health inequalities. Previous reports indicate that hill tribe children, especially age under 5 years, face social health disadvantages but little is known about the underlying causes. Exploring healthcare utilization among hill tribe children is therefore essential and it may well provide some insight. Methods A qualitative study was conducted using purposive sampling techniques to recruit participants based on our criteria. In-depth interviews and focus-group discussions were employed to explore the experiences of parents (n = 20), community leaders (n = 20), and healthcare providers (n = 20) when caring for children aged under 5 years. Interview transcripts were coded, and thematic analysis was then performed. Results The participants shared their experiences with accessing healthcare services in underserved areas. Barriers to access was the central theme identified. Sub-themes included: (1) distance matters, (2) education and socioeconomic deprivation, (3) lack of cultural sensitivity, (4) communication problems, (5) tradition, beliefs, and differences in cultural practice, (6) lack of child health professionals, and (7) bureaucratic hurdles. Conclusions Healthcare services and environments must be transformed to provide healthcare services, education, and information appropriate to the cultures and beliefs prevalent in the hill tribe population.